Chronic Recurrent Multifocal Osteomyelitis: A Diagnostic Dilemma. Issue 2 (April 2016) - Mallick, A.; Chaturvedi, A.; Muthukumar, N.
Abstract : Case: Chronic recurrent multifocal osteomyelitis, a misnomer in itself, is a rare disorder that presents infrequently to orthopaedic units. The differential diagnosis is wide, including neoplastic lesions and infection, which may lead to unnecessary interventional and surgical procedures. We present a case that exhibited the hallmark features of this condition—recurrent, multifocal, aseptic osteitis in a 9-year-old girl—and our rationalized management including imaging, nonsteroidal anti-inflammatory drugs, and bisphosphonates. Conclusion: With increased awareness by orthopaedic surgeons, patients may be diagnosed and managed appropriately, enabling a benign course and limiting morbidity.